2000
DOI: 10.1002/1096-9098(200005)74:1<11::aid-jso3>3.0.co;2-d
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of anal function after surgery for rectal cancer

Abstract: Anal sphincteric continence was better after surgery with a high or low colorectal anastomosis than after coloanal anastomosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
1
1

Year Published

2006
2006
2014
2014

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(18 citation statements)
references
References 7 publications
0
16
1
1
Order By: Relevance
“…To preserve continence, ultra low anastomoses are necessary after TME. Continence and quality of life are affected by the level of the straight anastomosis [2][3][4][5]18]. Associated problems can be improved by colonic J-pouch reconstruction [7][8][9][10][11][12][13]18].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…To preserve continence, ultra low anastomoses are necessary after TME. Continence and quality of life are affected by the level of the straight anastomosis [2][3][4][5]18]. Associated problems can be improved by colonic J-pouch reconstruction [7][8][9][10][11][12][13]18].…”
Section: Discussionmentioning
confidence: 99%
“…Bittdorf et al obtained similar results for their colopouch anal group after intersphinctal resection-55% of patients were incontinent for liquid stool at least once a week. Depending on the level of the anastomosis, Matteo et al reported good continence for 56% of their patients with a colorectal straight anastomosis and for 45% with a coloanal straight anastomosis [3]. Dehni et al showed that 45%-55% of their patients were incontinent for flatus [12].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In cases of cancer at low location, it is only allowable to resect the rectum along with part of the anus (particularly including the internal anal sphincter, but also with inclusion of the entire internal and part of the external anal sphincter), if this guarantees appropriate quality of the resection margin and preserves the efficiency of the sphincter apparatus to control defecation (10,11,12). Preservation of a rectal stump favours better bowel and gas continence (13).…”
Section: R E V I E W P a P E R Smentioning
confidence: 99%